Innovation capability and its role in enhancing the relationship between TQM practices and innovation performance - Maha Mohammed Yusr (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Innovation plays a critical role in predicting the long-term survival of organizations, determining an organization's success and sustaining its global competitiveness, especially in an environment where technologies, competitive position and customer demands can change almost overnight, and where the life-cycle of products and services are becoming shorter. Therefore, the main purpose of this paper is to extend the existing knowledge as to the relationship between TQM practices and innovation performance by exploring the expected role of innovation capability as mediator to enhance this relationship. At the same time, this study attempted to shed a light on how to improve innovation performance of manufacturing companies in Malaysia. The gained results indicated that innovation capability mediates the relationship between TQM practices and innovation performance. More importantly, this study supports the findings of the past studies that questioned the role of TQM practices in improving innovation performance. Finally, in light of the obtained results, several recommendations were introduced to assist decision makers in manufacturing companies.
Keywords: 650; Innovation performance; Innovation capability; TQM practices; RBV theory; Partial Least Square PLS